Electronic student worksheet based on computational thinking on arithmetic sequences and series - Tiara Rodiana Azma; Hapizah Hapizah; Darmawijoyo Darmawijoyo (Al-Jabar)
Background: The lack of learning media based on Computational Thinking (CT) for high school students, especially in the material arithmetic sequences and series, is one of the causes of students' low CT skills. Aim: This research was conducted to develop learning media in the form of Electronic Student Worksheets on the material of arithmetic series and sequences to improve CT skills by utilizing Liveworksheets media. Method: This research was conducted using a design research method, a development study type with the Tessmer development model. The focus is on the development of CT-based Electronic Student Worksheets. Result: The validation value of the developed CT-based Electronic Student Worksheets reached 95.47%, while the practicality assessment of CT-based Electronic Student Worksheets based on the questionnaire obtained a value of 89.97% Conclusion: Based on the results of the study, it can be concluded that the developed CT-based Electronic Student Worksheets meets the valid and practical criteria to be used in learning to improve CT skills and understanding of arithmetic sequences and series material for high school students.